Development of a dichotomous indicator for population-level assessment of the dietary diversity of women of reproductive age - Martin Prével, Y.; Arimond, M.; Allemand, P.; Wiesmann, D.; Ballard, T.J.; Deitchler, M.; Dop, M.C.; Kennedy, G.; Lartey, A.; Lee, W.T.K.; Moursi, Mourad (Elsevier, 2017)
Background: Dietary diversity is a key element of diet quality but diets of women of reproductive age (WRA; 15-49 y) in resource-poor settings are often deficient in a range of micronutrients. Previous work demonstrated relationships between simple food group diversity indicators (FGI) and micronutrient adequacy among WRA. For operational and advocacy purposes, however, there is strong demand for a dichotomous indicator reflecting an acceptable level of dietary diversity. Objective: To develop a dichotomous indicator of dietary diversity among WRA. Methods: We performed a secondary analysis of 9 data sets containing quantitative dietary data from WRA in resource-poor settings (N total = 4,166). From the raw dietary data we calculated an individual "mean probability of adequacy" (MPA) across 11 micronutrients. Several candidate FGI were constructed. Indicator performance in predicting MPA > 0.60 was assessed within each data set using receiver-operating characteristics (ROC) analysis and sensitivity/specificity analysis at various FGI cut-offs. The analysis was performed separately for non-pregnant and non-lactating (NPNL) and for lactating women. Results: We identified 2 "best candidate" dichotomous indicators based on 9- or 10-point food group scores (FGI-9 and FGI-10) with a cut-off of 5 food groups or more. Both were significantly correlated to MPA in each site (P < 0.001). Areas under the curve (AUC) were moderate, ranging from 0.62 to 0.82 among NPNL women and from 0.56 to 0.90 among lactating women. Comparisons of results slightly favored FGI-10 for all women. Conclusions: When resource-intensive dietary methods are not feasible, a simple dichotomous indicator based on a cut-off of >5 of 10 defined food groups reflects "Minimum dietary diversity for women of reproductive age" (MDD-W). According to the conclusions of a consensus meeting of experts, this indicator is well suited for population-level assessment, advocacy, and maybe also for tracking of change in dietary diversity across time.